Evaluation of the changes in pre-extraction blood pressure and pulse rate values with post-extraction blood pressure and pulse rate values - Saikhedkar, Rashmi; Jain, Samkit; Atre, Aditi; Kulkarni, Apurva (International Journal of Research in Medical Sciences, 2023)
Background: Aim and objectives were to compare the differences in blood pressure and pulse rate readings before and after extraction of a tooth. Methods: A total of 250 patients were selected for the study, out of which, 124 were males and 126 were females. All the patients were in an age group from 20 till beyond 73 years of age. Blood pressure and pulse rate readings were measured before the start of the procedure. Extraction procedure was performed and post extraction blood pressure and pulse rate values were recorded. Both the values were compared and evaluated. Results: There was an obvious increase in systolic blood pressure and pulse rate values after a tooth extraction. Conclusions: Blood pressure and pulse rate values showed changes before and after tooth extraction but were within normal limits.